2018
DOI: 10.1590/1678-992x-2016-0456
|View full text |Cite
|
Sign up to set email alerts
|

On the controlling of temperature: A proposal for a real-time controller in broiler houses

Abstract: Environmental conditions in broiler houses, specifically temperature, are key factors that should be controlled to ensure appropriate environment for broiler rearing. In countries with tropical/subtropical climate, like Brazil, high temperatures produce heat stress to animals, affecting the production process. This research proposes a real-time model to control temperature inside broiler houses. The controller is a self-correcting model that makes real-time decisions on the ventilation system operation (exhaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
(9 reference statements)
0
4
0
1
Order By: Relevance
“…At similar outdoor temperatures, the comparison of saturated and non-saturated cycles revealed that improved humidity management led to a saving of 17% in climate control energy during one cycle, which involved savings between 33% and 47% in energy consumption per kg of pig produced. Recent research points to the incorporation of advanced estimation techniques into complex control systems to achieve energy savings [24,29,30,42,43], or to the use of a large number of sensors in advanced technologies in order to consider animal welfare [44]. Yet, farms currently use control systems based on a single temperature probe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At similar outdoor temperatures, the comparison of saturated and non-saturated cycles revealed that improved humidity management led to a saving of 17% in climate control energy during one cycle, which involved savings between 33% and 47% in energy consumption per kg of pig produced. Recent research points to the incorporation of advanced estimation techniques into complex control systems to achieve energy savings [24,29,30,42,43], or to the use of a large number of sensors in advanced technologies in order to consider animal welfare [44]. Yet, farms currently use control systems based on a single temperature probe.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, postweaning facilities consist of many rooms, which requires installing a large amount of measurement and control devices on a single farm. Yet, environmental control has commonly been based on the use of data from a single temperature probe [24,25], whereas other variables such as humidity [26] or CO 2 [27,28] are of increasing interest because of their impact on swine production [29] and must be included in automation. A good control strategy can prevent some delayed control effects caused by time lags of devices and provide an expected in-time indoor thermal environment control [30].…”
Section: Introductionmentioning
confidence: 99%
“…Farmers can measure feed intake for individual cows and manage feed costs based on the demands of their animals with the help of RGB-D cameras (Detsch et al, 2018). We can precisely predict farm animal performance with the use of technology.…”
Section: Role Of Ai In Fcr Improvementmentioning
confidence: 99%
“…Accordingly, incorporating humidity as a control variable could contribute to improving the environmental controls in these buildings [117] by reducing the high humidity levels that result in condensation and are detrimental to heating efficiency [17,23]. Recent research points to the incorporation of advanced estimation techniques into complex control systems to achieve energy savings [113,114,[118][119][120], or to the use of a large number of sensors in advanced technologies in order to consider animal welfare [71,74,81,84,85,121]. Incorporating humidity as a control variable would involve higher ventilation rates, with positive consequences for animal welfare, a reduction in heating energy consumption and an improvement in productivity.…”
Section: Environmental Control Systemsmentioning
confidence: 99%